Adiposity in relation to readmission and all‐cause mortality following coronary artery bypass grafting: A systematic review and meta‐analysis. (3rd April 2019) - Zhang, Kefeng; Wang, Junjie; Yang, Yan; An, Ruopeng
Summary: This study systemically reviewed evidence linking adiposity to readmission and all‐cause mortality in post‐coronary artery bypass grafting (CABG) patients. Keyword/reference search was performed in PubMed, Web of Science, CINAHL, and Cochrane Library for articles published before June, 2018. Eligibility criteria included study designs: experimental/observational studies; subjects: adult patients undergoing CABG; and outcomes: hospital/clinic readmissions, and short‐term (≤30 days) and mid‐to‐long‐term (>30 days) all‐cause mortality. Seventy‐two studies were identified. Meta‐analysis showed that the odds of post‐CABG readmission among patients with overweight was 30% lower than their normal‐weight counterparts and the odds of mid‐to‐long‐term post‐CABG mortality among patients with overweight were 20% lower than their normal‐weight counterparts. In contrast, no difference in post‐CABG readmission rate was found between patients with obesity and their nonobese counterparts; no difference in short‐term or in‐hospital post‐CABG mortality rate was found between patients with overweight or obesity and their normal‐weight counterparts; and no difference in mid‐to‐long‐term post‐CABG mortality rate was found between patients with obesity and their normal‐weight counterparts. In conclusion, patients with overweight but not obesity had a lower readmission and mid‐to‐long‐term mortality rate following CABG relative to their normal‐weight counterparts. Preoperative weight loss may not be advised to patients with overweight undergoing CABG.